Pelaksanaan Quality Control yang Efektif sebagai Salah Satu Upaya untuk Mencapai Target Produksi pada Perusahaan CV.Weenee Anugerah Tekstil di Kota Malang - Cintia Anggraini; Wahju Wuladari; Mulyono Mulyono (Ebisnis Manajemen, 2024)
The aim of this research is to determine the effect of implementating Quality Coontrol on production effectiveness to achieve production targets at the company Cv.Weenee Anugerah Textile. The method ised this research is descriptive method with a quantitative approach. The research technique used for data collection was field research,while data analysis used a cause and effect diagram (fishbone chart).in this research,the results obtained show that the company has implemented quality control. If a company wants to impelement zero defects,it can use six sigma. Now the compny is currently still at level 4 sigma with a value 2993 DPMO,because to achieve six sigma need to reach a value of 3.4 DPMO.